If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = -14 + -6v Solving 0 = -14 + -6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '6v' to each side of the equation. 0 + 6v = -14 + -6v + 6v Remove the zero: 6v = -14 + -6v + 6v Combine like terms: -6v + 6v = 0 6v = -14 + 0 6v = -14 Divide each side by '6'. v = -2.333333333 Simplifying v = -2.333333333
| 9b=81 | | -x+4x=18 | | 2(2x-138)=x+24 | | 2x+3(.25x)=55 | | 4x+-8=18 | | 5f=-50 | | 4-6+5x= | | 4=-9 | | -7-(-8)=x | | 10.3x-32=-7x+28 | | (2x-(-4))(3x+(-2))=3-(5-3x)(2x+3) | | =h(a+b) | | -7-6=x | | 10x-11x+3=0 | | -9-3=x | | n-9=-42 | | -5(6m-3)=38-7m | | -10+4x=-42 | | 0.88=log(x) | | 2(9x+631)=2x+270 | | .88=log(x) | | 1-5b-4b=10 | | 11z=-100 | | 3n-9+3=24 | | 3(14-4y)-5y=-9 | | 6y+5=10y-1 | | 12k+14=10k-2k-7 | | -3(x+4)+16= | | J-8=-5 | | 10x-8=31.5 | | 2(2x-11)=2x | | 8x-4+8x-4+21+3=180 |